Strategi Gerakan Cegah Stunting Menggunakan Metode Sosialisasi di Desa Darakunci, Kabupaten Lombok Timur: Strategi Gerakan Cegah Stunting Menggunakan Metode Sosialisasi di Desa Darakunci, Kabupaten Lombok Timur - Nurul Fitri; Nabila Widiawati; Risma Pramudia Ningtyas; Farah Dhiyah Alfini Sarnyoto; Waridatun Nisa; Wahyu Ibnistnaini; Muhammad Dhani Ardha; Qurratul Aima; Salmanto Salmanto; Sopia Novitasari; Saprizal Hadisaputra (Program Studi Pendidikan Kimia FKIP Universitas Mataram, 2022)
ABSTRACTIndonesia still has a fairly high stunting prevalence rate, which is 24.4% and isstill at the standard number tolerated by WHO, which is below 20%. This is dueto the high rate of anemia and malnutrition in adolescent girls before marriage,so that during pregnancy they produce stunted children.Stunting is a condition of growth and development failure experienced by childrendue to lack of nutritional intake for a long time, repeated infections, andinadequate psychosocial stimulation, especially in the first 1000 days of life. Inthe short term, specific and sensitive nutrition interventions need to be optimized,while the long term strategy needs to be intensified with opportunities forcollaboration between sectors and multistakeholders to ensure sustainability andachieve the stunting reduction acceleration target. In addition, it is necessary toimplement the Public Private Partnership strategy in an effort to enforcegovernance, a commitment to operational elaboration is needed to ensure thestunting prevention program for rural toddlers at 1000 HPK.